The presence of PHB granules in cytoplasm protects non-halophilic bacterial cells against the harmful impact of hypertonic environments - Obruca, Stanislav; Sedlacek, Petr; Mravec, Filip; Krzyzanek, Vladislav; Nebesarova, Jana; Samek, Ota; Kucera, Dan; Benesova, Pavla; Hrubanova, Kamila; Milerova, Miluse; Marova, Ivana (New biotechnology, 2017)
Numerous prokaryotes accumulate polyhydroxybutyrate (PHB) intracellularly as a storage material. It has also been proposed that PHB accumulation improves bacterial stress resistance. Cupriavidus necator and its PHB non-accumulating mutant were employed to investigate the protective role of PHB under hypertonic conditions. The presence of PHB granules enhanced survival of the bacteria after exposure to hypertonic conditions. Surprisingly, when coping with such conditions, the bacteria did not utilize PHB to harvest carbon or energy, suggesting that, in the osmotic upshock of C. necator, the protective mechanism of PHB granules is not associated with their hydrolysis. The presence of PHB granules influenced the overall properties of the cells, since challenged PHB-free cells underwent massive plasmolysis accompanied by damage to the cell membrane and the leakage of cytoplasm content, while no such effects were observed in PHB containing bacteria. Moreover, PHB granules demonstrated "liquid-like" properties indicating that they can partially repair and stabilize cell membranes by plugging small gaps formed during plasmolysis. In addition, the level of dehydration and changes in intracellular pH in osmotically challenged cells were less pronounced for PHB-containing cultures, demonstrating the important role of PHB for bacterial survival under hyperosmotic conditions.
Keywords: fluoresceiny; Hydroxybutyrates; termogravimetrie; Crystallization; krystalizace; Thermogravimetry; Time Factors; hypertonické roztoky; mikrobiální viabilita; hydroxybutyráty; časové faktory; Microbial Viability; Cupriavidus necator; Fluoresceins; osmotický tlak; Poly(3-hydroxybutyrate); Stress conditions; elektronová kryomikroskopie; Hyperosmotic conditions; Hypertonic Solutions; fluorescenční mikroskopie; voda; Osmotic Pressure; Water; Microscopy, Fluorescence; cytoplazmatická granula; Plasmolysis; Cytoplasmic Granules; Cryoelectron Microscopy; PHB